Over 17% efficiency all-small-molecule organic solar cells based on an organic molecular donor employing a 2D side chain symmetry breaking strategy. Issue 10 (14th September 2022) - Li, Zhiya; Wang, Xunchang; Zheng, Nan; Saparbaev, Aziz; Zhang, Jiayi; Xiao, Cong; Lei, Shiyun; Zheng, Xufan; Zhang, Manxue; Li, Yuda; Xiao, Biao; Yang, Renqiang
Abstract : The 2D asymmetric side chain strategy via modification with different halogens can optimize the morphology, improve the molecular interaction and control the photophysical properties, promoting an outstanding PCE of 17.0% in binary ASM-OSCs. Abstract : The symmetry breaking strategy has been broadly applied in the design of organic photovoltaic materials; however, a comprehensive understanding of the effects of two-dimensional (2D) asymmetric side chains in all-small-molecule organic solar cells (ASM-OSCs) is rarely studied. Herein, a new building block based on an asymmetric 2D side chain with halogen modification was designed for the construction of small molecular donors to fine-tune bulk heterojunction thin films and electronic properties. In comparison with the symmetric BTR-Cl, its asymmetric counterparts, i.e., TB- and TB-F-based blends, exhibited the optimal hierarchical morphology with multi-scale domains, enhanced D/A molecular interactions and interfacial packing at the unilateral chain, and homogeneous vertical phase distribution. Transient absorption measurement revealed that an enhanced exciton diffusion coefficient and fast exciton dissociation process were achieved in the TB-F based device, enabling more percolation paths for charge transport, suppressed bimolecular recombination and reduced energy disorder. Consequently, a champion efficiency of 17.0% with a remarkably increased short-circuit current density and fill factor was recorded in the binary ASM-OSCs. Overall, this work elucidates the important 2D side chain symmetry breaking strategy, which precisely controls and optimizes the material properties and gives design inspiration for the future higher performance of ASM-OSCs.